Multi-stage fault formation and REE distribution in the surrounding Devonian dolomites in the south-eastern part of the Holy Cross Mountains (Poland) - Nieć, Marek; Pawlikowski, Maciej; Sermet, Edyta (Geology, Geophysics and Environment, 2024)
Metallogenic studies carried out in the Holy Cross Mountains indicate a relationship between mineralization and fault tectonics in Devonian formations. The impact of fault formation on the geochemistry of host rocks has not yet been studied. Mineralogical and geochemical studies of fault core gouges and damage zones in the fault walls of Devonian dolomites in the Budy and Jurkowice quarries were carried out. In the clay-carbonate filling of the fault fissure, the presence of two generations of Fe sulfides, the increased content of Zr, Nb, U and Th in relation to the surrounding rocks was noted. In the fault walls of the dolomites, iron sulfide and hematite mineralization were found. Research on the REE content indicates that it is lower in the fault walls than in those located far from it, while it is clearly higher in the fault gouge, especially in terms of the content of “heavy” elements (HREE). This indicates both the supply of some components to the fault zone from external sources and their displacement from the surrounding rocks. It was also found that the fault was renewed before and after the Neogene at least twice (Badenian)